Comparing and Contrasting the History of the Euro With the History of Accounting Convergence - Coyne, Michael P. (Journal of Accounting and Finance, 2020)
The purpose of this paper is to propose a theory that the historical development, the perceived/actual benefits and the problems of Accounting Convergence are somewhat parallel to the historical development, perceived/actual benefits and problems of the Euro. In addition, the paper provides a concise summary and analysis of the fifty year history of International Accounting Standard Convergence while simultaneously intertwining certain aspects of the history of the Euro’s development.